Study of hydrogen adsorption on Pt/WO3-ZrO2 through Pt sites - Triwahyono, Sungeng; Abdul Jalil, Aishah; Hattori, Hideshi (Elsevier B.V., 2007)
The rate determining step and the energy barrier involved in hydrogen adsorption on Pt/WO3ZrO2 were studied based on the assumption that the hydrogen adsorption occurs only through Pt sites. The rate of hydrogen adsorption on Pt/WO3-ZrO2 was measured in the adsorption temperature range of 323-573 K and an initial hydrogen pressure of 50 Torr. The rates of hydrogen uptake were very high for the initial few minutes and the adsorption continued for more than 5 h below 523 K. The hydrogen uptake far exceeded the H/Pt ratio of unity for all adsorption temperatures, indicating that the adsorption of hydrogen involved the dissociative adsorption of hydrogen on Pt sites to form hydrogen atoms, the spillover of hydrogen atoms onto the surface of the WO3-ZrO2 catalyst, the diffusion of spiltover hydrogen atom over the surface of the WO3-ZrO2 catalyst, and the formation of protonic acid site originated from hydrogen atom by releasing an electron in which the electron may react with a second hydrogen atom to form a hydride near the Lewis acid site. The rate determining step was the spillover with the activation energy of 12.3 kJ/mol. The rate of hydrogen adsorption cannot be expressed by the rate equation based on the assumption that the rate determining step is the surface diffusion. The activity of Pt/WO3-ZrO2 was examined on n-heptane isomerization in which the increase of hydrogen partial pressure provided positive-effect on the conversion of n-heptane and negative-effect on the selectivity towards iso-heptane.